Hove To: Missing the Storm in the Lee of Life - Peters, Christopher Thomas (The Trumpeter, 2015)
We live in a time when, increasingly, we don’t have to face the wider world. As an educator in Newfoundland I have been dismayed to find that time in seats has become synonymous with learning. Worse still, when young people do have time to themselves they rarely trudge into the admittedly fickle moods of Newfoundland’s weather. Lost then is an intimate feel and connection to place, as well as the skills to negotiate and find safe passage through the worst of weather’s onslaught. These were once skills that were important. In order to counter Barry Lopez’s quote that our communities and places are at best “selectively known” we must make Nature our teacher. Even when it requires full weather-gear to make it to ‘class’.